Perspektywy rozwoju ekologicznej hermeneutyki Biblii - Twardziłowski, Tomasz (Verbum Vitae, 2017)
The aim of this article is to provide biblical scholars with a broad framework concerning the emerging field of “ecological hermeneutics” of the Bible, a very popular approach nowadays. This article examines whether it is only a temporarily fashionable phenomenon or a truly important trend for current and future research. There are presently three main streams of this interpretative approach, whose theoretical and methodological assumptions represent both different starting points and different objectives for biblical interpretation. The most popular, the apologetic form, often simplifies and distorts the meaning of the text and fails to provide credible answers to the modern reader. The radical form departs from hermeneutics and moves toward the deconstruction of the Bible and the reconstruction of a hypothetical biblical text. The neo-orthodox (revisionist) form is judged the most promising for the further development of ecological hermeneutics, as it allows exploration of the multitude of meanings of the biblical text and also of the traditions of its interpretation. It is a useful tool in the search for a better understanding of the proper relationship of man with the created world – the world in which he lives, is to be saved and which he is called to protect. It is hoped that the proposed study will help expand the research horizons of Polish exegesis.